HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN MORALE KERJA PADA KARYAWAN BALAI BESAR LATIHAN KERJA INDUSTRI (BBLKI) SURAKARTA - Wahyuningsih, Triani (Universitas Sahid Surakarta, 2014)
Important source in any company or organization is human. This study aims to determine 1) the relationship between emotional intelligence with work on employee morale, 2) the role of emotional intelligence to work morale, 3) the level of emotional intelligence on the subject of research, 4) the level of morale working on research subjects. The hypothesis is a positive relationship between emotional intelligence with work on employee morale. Subjects in this study were employees of Center for Industrial Training (BBLKI) Surakarta. The population of 120 people. The samples in this study using purposive sampling, with the characteristics of the study subjects: 1) subjects aged between 30-60 years, 2) Working period between 20 s / d 40 years. Subject retrieval technique used is nonrandom sampling. Based on calculations using analytical techniques derived product moment coefficient (r) of 0.296 with p = 0.020 (p <0.05). This means the hypothesis is accepted that there is a significant positive relationship between emotional intelligence with work on employee morale. That is emotional intelligence veriable depat used as a predictor for predicting work on employee morale.